2023
DOI: 10.1186/s12893-023-01978-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative fluid balance during pancreatoduodenectomy on postoperative pancreatic fistula: an observational cohort study

Abstract: Background Perioperative fluid management during major abdominal surgery has been controversial. Postoperative pancreatic fistula (POPF) is a critical complication of pancreaticoduodenectomy (PD). We conducted a retrospective cohort study to analyze the impact of intraoperative fluid balance on the development of POPF. Methods This retrospective cohort study enrolled 567 patients who underwent open pancreaticoduodenectomy, and the demographic, labo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The study found that fluid balance was significantly associated with the development of POPF, highlighting the importance of appropriate fluid management in pancreatic surgery. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that fluid balance was significantly associated with the development of POPF, highlighting the importance of appropriate fluid management in pancreatic surgery. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The study found that fluid balance was significantly associated with the development of POPF, highlighting the importance of appropriate fluid management in pancreatic surgery. 31 In addition, questions are raised about what the optimal goals of hemodynamic parameters (healthy population-derived normal values, preoperative values, maximal values) should be. Studies have shown that optimising cardiac output and oxygen delivery to higher values intraoperatively (supranormal) did not affect postoperative complications rate, intensive care unit stay, or hospital stay length.…”
Section: Fluid Optimisation Strategymentioning
confidence: 99%